PRODUKSI GAS KARBON DIOKSIDA SELAMA PROSES BIOREMEDIASI LIMBAH HEAVY OIL DENGAN TEKNIK LANDFARMING - Charlena, Charlena; Mas?ud, Zainal Alim; Anas, Iswandi; Setiadi, Yadi; Yani, Moh. (CHEMISTRY PROGRESS, 2010)
Bioremediation is defined as biological degradation process of organic or inorganic wastes in a controlledcondition to control and reduce their amount in the environment. In this study, the soil which had been polutedby heavy petroleum oil fractions, i.e. heavy oil waste (HOW), was used as sample. The bioremediationtechnique used in this study is an ex-situ technique. This study was conducted to determine the amount ofproduced CO2 gas during the HOW degaradation process. Treatment of heavy oil waste with biostimulation andbioaugmentation. Production of CO2 gas were placed in impiger and analysis with titrimetry method. The highestCO2 production mean was obtained from the bioaugmentation treatment with compost adding, i.e. 244,5 mg/m3.Generally, graphs CO2 gas production followed a similar sinusoidal pattern. From these results it can beinfered that the degradation process of HOW happened during the treatments in aerobic condition.